(untitled) (Proceeding of the International Conference on Arts and Humanities, 2018)
As informal communities become villages, villages become townships and townships become cities. The importance of living in a structured society with better social services becomes a priority in many communities. Living in a society that has improved road infrastructures, accessible hospitals, and affordable education for citizens has become a key part of modern life. However, the more advanced societies become, the less indigenous cultural heritage knowledge a society consumes. Indigenous African music heritage becomes irrelevant in changing societies, and it becomes a victim of changing societies by default. Education systems from basic to advanced level are moving with global trends and there is no space for indigenous cultural knowledge. There is no interest to study such knowledge, particularly from the younger generation. As people migrate from rural to urban settlements in search of jobs and a better life, indigenous African music heritage is less practiced by many communities. Urbanisation makes indigenous music heritage look less formal to its own people, due to social changes. Communities that practise indigenous music heritage become fewer and fewer as urbanisation takes precedence in many societies. Documenting indigenous African sheet music for teaching and learning it is the best way to preserve such diminishing heritage practice.